Key Factors Influencing Instructor Performance at the Semarang Vocational Training and Productivity Center - Aryandhi, Erki; Indarto, Indarto; Santoso, Djoko (LPPM Institut Bisnis dan Informatika Kesatuan, 2024)
This study analyzes the influence of individual characteristics, organizational commitment, and work motivation on instructors' work performance, with work discipline as a moderating variable. The study was conducted at the Semarang Vocational and Productivity Training Center, using a quantitative method with data from 75 instructors through a Google Form-based questionnaire. Data collection took place for 14 days in June-July 2024. The analysis used moderated regression with SPSS version 26. The results showed that individual characteristics, organizational commitment, and work motivation had a significant influence on work performance. However, work discipline did not moderate the relationship between work motivation and work performance. However, work discipline strengthened the influence of individual characteristics and organizational commitment on performance. These findings indicate that instructors with high work motivation are able to achieve optimal performance without the need for additional reinforcement from work discipline.